Dissociating the Detection of Intentionality from Animacy in the Right Posterior Superior Temporal Sulcus - Gao, Tao; Scholl, Brian J.; McCarthy, Gregory (The Journal of neuroscience, 2012)
Certain motion patterns can cause even simple geometric shapes to be perceived as animate. Viewing such displays evokes strong activation in temporoparietal cortex, including areas in and near the (predominantly right) posterior superior temporal sulcus (pSTS). These brain regions are sensitive to socially relevant information, but the nature of the social information represented in pSTS is unclear. For example, previous studies have been unable to explore the perception of shifting intentions beyond animacy. This is due in part to the ubiquitous use of complex displays that combine several types of social information, with little ability to control lower-level visual cues. Here we address this challenge by manipulating intentionality with parametric precision while holding cues to animacy constant. Human subjects were exposed to a “wavering wolf” display, in which one item (the wolf) chased continuously, but its goal (i.e., the sheep) frequently switched among other shapes. By contrasting this with three other control displays, we find that the wolf's changing intentions gave rise to strong selective activation in the right pSTS, compared with (1) a wolf that chases with a single unchanging intention, (2) very similar patterns of motion (and motion change) that are not perceived as goal-directed, and (3) abrupt onsets and offsets of moving objects. These results demonstrate in an especially well controlled manner that right pSTS is involved in social perception beyond physical properties such as motion energy and salience. More importantly, these results demonstrate for the first time that this region represents perceived intentions beyond animacy.